Development Path to Participatory Community Along the Road. Royal Land No.12 (Phitsanulok - LomSak) / การพัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชนตามเส้นทางถนนหลวงแผ่นดินหมายเลข 12 (พิษณุโลก - หล่มสัก) - จิรวัฒน์ พิระสันต์, ณัฐทรัชต์ ชามพูนท์ และณัฐวัฒน์ วัฒนาประสิทธิ์, Jirawat Phirasant, Natharatt Charmpoonod (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 3 (2558): September - December 2015, 2015)
การวิจัยในครั้งนี้เป็นการพัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชนตามเส้นทางถนนหลวงแผ่นดินหมายเลข 12 (พิษณุโลก - หล่มสัก) โดยวัตถุประสงค์ของการวิจัย เพื่อรวบรวมองค์ความรู้ที่เกี่ยวกับแหล่งท่องเที่ยวของชุมชน พัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชน และเพื่อเสนอยุทธศาสตร์และข้อเสนอเชิงนโยบายการพัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชน คณะนักวิจัยได้จัดให้มีการศึกษาวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม ซึ่งประกอบด้วยการดำเนินกิจกรรมเชิงวิชาการและการพัฒนา เช่นสำรวจและเก็บข้อมูลภาคสนาม การประชุม สัมมนาร่วมกับตัวแทน ชุมชน ภาคีที่เกี่ยวข้อง เพื่อประสานความร่วมมือในการพัฒนา การประเมินผลก่อนการดำเนินโครงการและกิจกรรมย่อย จัดทำแผนและโครงการพัฒนาการท่องเที่ยวของชุมชน ประกอบด้วย การวิจัยครั้งนี้ พบว่า องค์ความรู้ที่เกี่ยวกับแหล่งท่องเที่ยวของชุมชน เป็นการวางแผนพัฒนาแหล่งท่องเที่ยวเริ่มจากการสืบค้นและ การวิเคราะห์แหล่งท่องเที่ยว ซึ่งรวมถึงความพร้อมของแหล่งท่องเที่ยวที่เอื้ออำนวยต่อการพัฒนา การปรับปรุง คุณค่าของแหล่งท่องเที่ยว  อันจะส่งผลถึงการดึงดูดใจนักท่องเที่ยวให้เดินทางไปยังแหล่งท่องเที่ยวนั้น ซึ่งรวมถึงภาพรวมด้านความสวยงาม ลักษณะเด่น อัตลักษณ์ ความสำคัญทางประวัติศาสตร์ ความสำคัญทางศาสนา สภาพภูมิทัศน์ และวิถีชีวิต การพัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชน ได้แก่ สภาพการเข้าถึงแหล่งท่องเที่ยว  ระบบฐานข้อมูลทางอินเทอร์เน็ต การสร้างจุดหมายตาที่เชื่อมโยงชุมชน พัฒนาระบบบริการนำเที่ยวและมัคคุเทศก์ พัฒนาร้านขายของที่ระลึกและสินค้าพื้นเมือง ระบบความปลอดภัย โครงข่ายกิจกรรมการท่องเที่ยว การพัฒนาข้อมูลสื่อสิ่งพิมพ์ การโฆษณาและการสื่อสาร รวมทั้งประเมินความพึงพอใจของนักท่องเที่ยวที่มีต่อการดำเนินงานของโครงการโดยใช้แบบสอบถาม ประเมินผลหลังการดำเนินโครงการและกิจกรรมย่อยต่างๆ สำหรับยุทธศาสตร์และข้อเสนอเชิงนโยบายการพัฒนาเส้นทางการท่องเที่ยวแบบมีส่วนร่วมโดยชุมชน ประเด็นสำคัญ คือ ต้องสามารถจัดการสิ่งอำนวยความสะดวกเบื้องต้น เช่น ถนน ไฟฟ้า น้ำประปา การจัดการขยะ ระบบสื่อสารคมนาคม ลานจอดรถ ที่พักโรงแรม ร้านอาหาร และร้านขายของที่ระลึกให้พอเพียงกับจำนวนนักท่องเที่ยว รวมถึงต้องควบคุมจำนวนนักท่องเที่ยวในพื้นที่ดังกล่าว ตลอดจนปัญหาและผลกระทบที่จะตามมาจากการพัฒนาการท่องเที่ยวในพื้นที่ และจัดประชุมเพื่อเผยแพร่ผลงานวิจัยสู่สาธารณะ   คำสำคัญ : การท่องเที่ยว  มีส่วนร่วม  เส้นทางหมายเลข 12    Abstract This research work is the development of the community-participatory tourism route along No.12 Highway (Pitsanulok-Lomsak). The main objectives of this research work are to accumulate knowledge about tourist attractions in the local communities, to develop the community-participatory tourism route and to suggest strategy and policy relevant to the development of community-participatory tourism route. The research team runs the participatory research operation that is comprised of academic and developmental activities such as the survey and field data collection works, and the meetings and seminars with representatives from the communities and other related parties in order to attain collaboration, and the evaluation before the program and activities are carried out, and the making of plans and the community tourism development project. The findings from this research reveal that the knowledge about the tourist attractions in the community is about the planning for the development of such tourist attractions. The planning process starts with the identification and analyses on local tourist attractions. This includes the preparation of the tourist attractions, which will facilitate the development, improvement and value of the tourist attractions, which will enable the tourist attractions to actually attract tourists. The important matters include the beauty, the uniqueness, the identification, the historical and religious importance, the landscapes and local people’s way of life.                                      The development of community-participatory tourism route incorporates the accessibility of tourist attractions, internet database systems, the establishment of landmarks that are linked to local communities, the development of touring system and tour guides,  the development of souvenir and local product shops, security systems, the tourism activity network, the printed media, advertisements and communication, as well as the assessment of tourists’ satisfaction towards the project through questionnaire and to evaluate the results after the implementations of the project or sub-activities.  Concerning the strategy and policy suggestions for the development of the tourism route, the major concern is to provide and manage infra-structures such as roads, electricity, water supply, garbage management, telecommunication system, parking space, accommodations, restaurants and souvenir shops in order to support the tourists. In addition, there must be the control over the number of tourists in the area, as well as other issues and effects from the development of the tourism in the area. There must also be meetings held for publicizing the findings from the research.     Keywords: Tourism, Community, Route Along No.12 (Phitsanulok-Lomsak)
Keywords: การท่องเที่ยว มีส่วนร่วม เส้นทางหมายเลข 12 Tourism, Community, Route Along No.12 (Phitsanulok-Lomsak)